Phosphoric acid pretreatment of poplar to optimize fermentable sugars production based on orthogonal experimental design - Chen, Deming; Tang, Wenjing; Wang, Hui; Sheng, Yequan; Tan, Xin; Shi, Yang; Fan, Wei; Ge, Shengbo (Frontiers in Chemistry, 2023)
The recalcitrant structure of raw poplar limited the production of fermentable sugars when applied as the material in the pretreatment of biochemical conversions. Phosphoric acid pretreatment is an efficient method to destroy the compact lignocellulose matrix presence in the poplar. In this study, phosphoric acid pretreatment of poplar was optimised by an orthogonal experimental design [L9(33)] to improve enzymatic digestibility through investigating the effects of reaction temperature, time duration, and phosphoric acid concentration. The optimal conditions were selected based on the variance of chemical compositions, hemicellulose removal ratio, and delignification of the woody material after pretreatment. The optimum enzymatic hydrolysis yield of up to 73.44% was obtained when the phosphoric acid pretreatment performed at 190°C for 150 min under 1.5% of v/v phosphoric acid concentration.